2015
DOI: 10.1186/s12868-015-0229-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel zebrafish (Danio rerio) gene, wdr81, associated with cerebellar ataxia, mental retardation and dysequilibrium syndrome (CAMRQ)

Abstract: BackgroundWDR81 (WD repeat-containing protein 81) is associated with cerebellar ataxia, mental retardation and disequilibrium syndrome (CAMRQ2, [MIM 610185]). Human and mouse studies suggest that it might be a gene of importance during neurodevelopment. This study aimed at fully characterizing the structure of the wdr81 transcript, detecting the possible transcript variants and revealing its expression profile in zebrafish, a powerful model organism for studying development and disease.ResultsAs expected in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…We found that CSN2 was mostly related to immunocompetence and development (Cui et al, ). PKD1 was related to sclerotin development (Xiao et al, ), MX1 was also related to immunocompetence (Haller, Arnheiter, Gresser, & Lindenmann, ; Pichlmair et al, ), GRIN3B and HCFC1 were related to brain development (Hornig et al, ; Jolly et al, ), RANBP9 was related to neurodevelopment, RICTOR was related to muscle development (Suryawan et al, ), as well as WDR81 was related to heart, eyes, and neurodevelopment (Doldur‐Balli et al, ; Traka et al, ). In transitional milk, a total of six peptides derived from four proteins were both located in domains and predicted to be related to neonatal immunity and organ development such as CSN2 and PVRIG were related to immunocompetence and development (Cui et al, ; Levy et al, ), HNRNPK was related to lung development (Yang et al, ), PRDM13 was related to eyes development and lipid metabolism (Manes et al, ; Satoh, Brace, Rensing, & Imai, ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that CSN2 was mostly related to immunocompetence and development (Cui et al, ). PKD1 was related to sclerotin development (Xiao et al, ), MX1 was also related to immunocompetence (Haller, Arnheiter, Gresser, & Lindenmann, ; Pichlmair et al, ), GRIN3B and HCFC1 were related to brain development (Hornig et al, ; Jolly et al, ), RANBP9 was related to neurodevelopment, RICTOR was related to muscle development (Suryawan et al, ), as well as WDR81 was related to heart, eyes, and neurodevelopment (Doldur‐Balli et al, ; Traka et al, ). In transitional milk, a total of six peptides derived from four proteins were both located in domains and predicted to be related to neonatal immunity and organ development such as CSN2 and PVRIG were related to immunocompetence and development (Cui et al, ; Levy et al, ), HNRNPK was related to lung development (Yang et al, ), PRDM13 was related to eyes development and lipid metabolism (Manes et al, ; Satoh, Brace, Rensing, & Imai, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the absence of absent interaction with pressure x n-back cannot be explained by low salience of the pressure stimulus. However, using constant tactile pressure stimulation in a block design is of risk for a fast adaptation to this stimulus [67]. In this way, the onset of tactile pressure occurrence can be detected in order to report a pressure block, but will not remain an effective distractor during the course of the visual n-back stimulus sequence, with likely effects to both, behavioral performance and brain activity.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In this way, the onset of tactile pressure occurrence can be detected in order to report a pressure block, but will not remain an effective distractor during the course of the visual n-back stimulus sequence, with likely effects to both, behavioral performance and brain activity. Therefore, the negative results could also be caused by the experimental limitations due to a possible fast reduction of the tactile salience due to sensory adaptation during the course of a single pressure block [67]. Possible experimental improvements for further directions could be providing randomized tactile pressure trials instead of pressure blocks and analyzing the data according to the expected tactile pressure adaptation (i.e.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%